Antiischemic effects of metoprolol and the risk of carbohydrate metabolism disturbances in angina patients - E. V. Bochkareva; O. V. Alexandrovich; P. Yu. Bardybakhin; E. K. Butina; N. G. Kucheryavaya; I. N. Ozerova; V. A. Metelskaya (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To study the association between antiischemic effects (AIE) of metoprolol (MP), glucose tolerance, and insulin sensitivity in patients with stable angina (SA). Material and methods. The study included 28 male patients, aged 46-68 years, with stable effort angina, Functional Class II-III, and positive exercise stress test (EST). The time of the ST segment depression by ≥1 mm defined the threshold exercise stress time. MP in a selected dose was administered twice a day, for one month. Its hemodynamic effects were assessed by the dynamics of heart rate (HR), blood pressure (BP), and double product (DP). Glucose tolerance test (GTT) was performed at baseline (before MP administration) and after one month of MP treatment. Tissue insulin sensitivity and insulin resistance (IR) were assessed by ISI0.120 and HOMA-IR parameters, respectively. Results. AIE was registered in 57% of the patients, while 43% failed to demonstrate it. Both groups did not differ by the extent of MP impact on the levels of HR, BP, and DP. The presence or absence of AIE was linked to selected parameters of glucose metabolism. In patients with AIE, the pre-treatment levels of glucose and insulin 2 hours after glucose load were higher (p=0,028 and 0,043, respectively) and ISI1,120 values lower than in patients without AIE (p=0,023). Among participants with AIE, impaired glucose tolerance (IGT) was observed in 4 at baseline and in 8 one month later; among patients without AIE, IGT was not registered. Conclusion. For the first time, the presence of AIE during MP therapy of SA patients was linked to the decreased insulin sensitivity of peripheral tissues (ISI0.120). Paired EST with a single MP dose at baseline provides an opportunity to identify the patients with a higher risk of metabolic disturbances during the longer-term MP treatment.